(untitled) (Global Journal of Human-Social Science, 2014)
Anthropocentrism magnifies the importance of existence in relation to man’s essence. This degrades the generic essence of the man and his genuine need for nature. The principles of sustainable development are at stake. The way modern man lives and works stands in deep contrast with these principles. Thus, the central issue of sustainable development is: where are the causes of alienation of modern man from the principles of sustainable development? For the answers h ave to l ook at human nature and the nature of the human community. Their synthesis may direct socio anthropogenesis of modern man in the direction of accepting the principles of sustainable, that is responsible development, in which the principle of needs is more important than the need itself.